Hydrogen bioproduction with Enterobacter sp. isolated from brewery wastewater - Maintinguer, Sandra Imaculada [UNESP]; Lazaro, Carolina Zampol; Pachiega, Renan [UNESP]; Varesche, Maria Bernadete Amâncio; Sequinel, Rodrigo; de Oliveira, José Eduardo [UNESP] (Elsevier, 2017)
Hydrogen-producing bacterial strains were isolated from granular sludge from a UASB reactor that treats brewery wastewater. Most of the isolated strains were related to the Enterobacter genus through a phylogenetic analysis of the 16S rRNA sequences. The strains could use various carbon sources (sugars and glycerol) to produce hydrogen. The isolated strain, identified as Enterobacter sp. based on 16S rRNA gene sequencing, produced 6.8 mmol H2 L−1culture medium when growing on glucose (2.0 g L−1) in anaerobic conditions at 30 °C. The main liquid metabolites were acetic acid (367 mg L−1), methanol (437 mg L−1) and ethanol (1101.26 mg L−1), after 9 h of fermentation. The maximum hydrogen yield of 0.8 mol H2/mol glucose was observed, indicating that Enterobacter sp. isolated from brewery wastewater was an efficient hydrogen-producing bacterium under mesophilic conditions.
Keywords: Bio H2; Brewery wastewater; Dark fermentation; Enterobacter sp.; Mesophilic conditions; Roll tubes